The Influence Of Service Quality On Consumer Loyalty In Cafe Jseven Pekanbaru - Fitriani, Roza; Assyifa, Zubaidah (EL-EMIR Institute, 2024)
The purpose of this research is to determine the effect of service quality on consumer loyalty at Cafe Jseven Pekanbaru. This research method uses a quantitative analysis method by means of which the data obtained is analyzed using statistical analysis techniques. The analytical technique used to test this research hypothesis is simple regression analysis. This technique is used to analyze independent variables against the dependent variable and can also show the direction of the relationship between the dependent variable and the independent variable using the SPSS application. Based on the research results that have been explained regarding the influence of service quality on consumer loyalty, it can be concluded that product quality with a calculated t value of 4.841 and a t table value of 1.984 so that t calculated 4.841 > t table 1.984 and a significant level of 0.000 < 0.05 means that the quality variable service partially influences consumer loyalty.